Heartwood extract from Dalbergia sissoo promotes fracture healing and its application in ovariectomy-induced osteoporotic rats. (30th June 2017) - Karvande, Anirudha; Khedgikar, Vikram; Kushwaha, Priyanka; Ahmad, Naseer; Kothari, Priyanka; Verma, Ashwni; Kumar, Padam; Nagar, Geet Kumar; Mishra, Prabhat Ranjan; Maurya, Rakesh; Trivedi, Ritu
Abstract: Objectives: This study was undertaken to investigate the effects of a heartwood ethanolic extract (HEE) made from the Dalbergia sissoo on facture healing and in the prevention of pathological bone loss resulting from estrogen deficiency in ovariectomized (Ovx) rats. Methods: Heartwood ethanolic extract (250, 500 and 1000 mg/kg per day) was administered orally immediately next day after drill-hole injury and continued for 2 weeks. Ovx rats received HEE at same doses for 12 weeks and compared with 17-β estradiol (E2; 100 μg/kg for 5 days/week subcutaneously) group. Confocal imaging for fracture healing, micro-architecture of long bones, biomechanical strength, formation of mineralized nodule by bone marrow osteoprogenitor cells, bone turnover markers and gene expression were studied. One-way ANOVA was used to test significance. Key findings: Heartwood ethanolic extract treatment promoted fracture healing, formation of new bone at the drill-hole site and stimulated osteogenic genes at callus region. HEE administration to the Ovx rats exhibited better micro-architectural parameters at various anatomical positions, better bone biomechanical strength and more osteoprogenitor cells in the bone marrow compared with Ovx + vehicle group. HEE exhibited no uterine estrogenicity. Conclusions: Oral administration of HEE was found to promote fracture healing and exhibited osteoprotective effect by possibly stimulation of osteoblast function.